Inhibition of Mitochondrial Biosynthesis Using a "Right‐Side‐Out" Membrane‐Camouflaged Micelle to Facilitate the Therapeutic Effects of Shikonin on Triple‐Negative Breast Cancer (Adv. Healthcare Mater. 18/2022). Issue 18 (20th September 2022) - Peng, Jianqing; Hu, Xiaoxia; Fan, Shuangqin; Zhou, Jia; Ren, Shuang; Sun, Runbin; Chen, Yi; Shen, Xiangchun; Chen, Yan
Abstract : Biomimetics In article number 2200742 by Yi Chen, Xiangchun Shen, Yan Chen, and co‐workers, a "right‐side‐out" membrane‐cloaking micelle is engineered for mitochondria‐targeted delivery of shikonin. Inspired by the stories from "Journey to the West", the monkey king blowing the camouflaged blue elixir to put out a fire is used to represent targeted delivery of shikonin to mitochondria that improves its therapeutic effects on triple‐negative breast cancer.